Phase stability of γ′-Ni2Cr and α-Cr in the Ni-Cr binary. (15th September 2018) - Miller, Cody; Field, Robert; Kaufman, Michael
Abstract: The stability of the γ′-Ni2 Cr long-range order (LRO) phase present on the Ni-Cr binary phase diagram was examined in a Ni-55Cr (wt. %) alloy. It is shown that the γ′-Ni2 Cr phase is metastable, and that the two-phase γ-Ni + α-Cr phase field extends to room temperature. The as-cast alloy consisted of a typical dendritic microstructure, with Cr-rich primary α-Cr dendrites and a Cr-lean, γ-Ni interdendritic. Annealing the as-cast alloy at 500 °C for 1000 h (γ′-Ni2 Cr + α-Cr phase field) resulted in pockets of α-Cr and γ-Ni + γ′-Ni2 Cr at the dendritic/interdendritic interface, with little change to the interdendritic γ-Ni microstructure. Annealing at 900 °C for 4 h (γ-Ni + α-Cr phase field) resulted in the interdendritic precipitation of α-Cr, both as a continuous and discontinuous precipitate. Annealing at 900 °C for 4 h followed by 500 °C for 1000 h resulted in the interdendritic precipitation of α-Cr at 900 °C, but no precipitation of γ′-Ni2 Cr during subsequent annealing at 500 °C. This behavior suggests that the γ′-Ni2 Cr phase is not the equilibrium phase, but rather a metastable transition phase. Furthermore, it is speculated that this phase in more complex alloys (i.e. Alloy 690) is also metastable, and its metastability should be considered in applications involving long-term, high temperature exposures. Graphical abstract: Image 1